Resiliency, Stress, and Culture Shock: Findings from a Global Health Service Partnership Educator Cohort. Issue 1 (30th November 2021) - Mitha, Kiran; Sayeed, Sadath Ali; Lopez, Maria
Background: Global health field assignments for medical and nursing professionals include a wide variety of opportunities. Many placements often involve individuals practicing in settings very different from their home environments, relying on their professional experience to help bridge cultural and clinical divides. Objectives: There is limited information about the individual factors that might lead to successful longer-term global health experiences in non-disaster settings. In this paper, we report on one cohort of health professionals' experiences of culture shock, stress, and resiliency as volunteers within the Global Health Service Partnership (GHSP), a public-private collaboration between Seed Global Health, the US Peace Corps, and the US Presidents Plan for Emergency Aids Relief (PEPFAR) that placed American medical and nursing educators in five African countries facing a shortage of health professionals. Methods: Using the tools of Project PRIME (Psychosocial Response to International Medical Electives) as a basis, we created the GHSP Educator Support Survey to measure resiliency, stress, and culture shock levels in a cohort of GHSP volunteers during their year of service. Findings: In our sample, participants were likely to experience lower levels of resiliency during initial quarters of global health placements compared to later timepoints. However, they were likely to experience similar stress and culture shock levels across quarters. Levels of preparedness and resources available, and medical needs in the community where the volunteer was placed played a role in the levels of resiliency, stress, and culture shock reported throughout the year. Conclusion: The GHSP Educator Support Survey represented a novel attempt to evaluate the longitudinal mental well-being of medical and nursing volunteers engaged in intense, long-term global health placements in high acuity, low resource clinical and teaching settings. Our findings highlight the need for additional research in this critical area of global health.